2000
DOI: 10.1111/1467-9507.00117
|View full text |Cite
|
Sign up to set email alerts
|

When Does Parents’ Differential Treatment Have Negative Implications for Siblings?

Abstract: We compared the extent of parents' differential treatment (PDT) and girls' and boys' perceptions of parents' fairness in middle childhood and adolescence as a function of the gender constellation of the sibling dyad. Further, we examined links between PDT in three domains, parental warmth, parents' temporal involvement, and the allocation of household tasks, and both siblings' self esteem and positivity in the sibling relationship. Participants were mothers, fathers and both first-and secondborn siblings from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
235
4
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(264 citation statements)
references
References 29 publications
19
235
4
5
Order By: Relevance
“…These findings raise the question of why paternal disfavoring and not maternal disfavoring was linked to narcissism and sibling warmth. McHale et al (2000) give some support to our findings; they reported that lower levels of fathers' involvement, warmth, and disfavoring of their adolescents participants were associated with lower levels of self-esteem. In this vein, it worth mentioning McCoy (1992, 1994), whose studies reported that the effects of the father's differential parenting accounted for unique effects in sibling relationships more often than the mother's differential parenting and that the father's unequal treatment was associated with negative sibling relationships.…”
Section: Parental Favoritism Narcissism and Sibling Relationshipssupporting
confidence: 86%
See 1 more Smart Citation
“…These findings raise the question of why paternal disfavoring and not maternal disfavoring was linked to narcissism and sibling warmth. McHale et al (2000) give some support to our findings; they reported that lower levels of fathers' involvement, warmth, and disfavoring of their adolescents participants were associated with lower levels of self-esteem. In this vein, it worth mentioning McCoy (1992, 1994), whose studies reported that the effects of the father's differential parenting accounted for unique effects in sibling relationships more often than the mother's differential parenting and that the father's unequal treatment was associated with negative sibling relationships.…”
Section: Parental Favoritism Narcissism and Sibling Relationshipssupporting
confidence: 86%
“…The favored sibling would be the one likely to experience guilt toward or contempt for the disfavored brother or sister who, in turn, is likely to experience feelings of anger, resentment, and jealously toward the favored sibling (Angel, 2006;Brody, 1998). Disparities in parents' affection for and warmth toward different children in the family, and differences in how restrictive and punitive parents are toward each child, have been shown to undermine the quality of the sibling relationship during childhood and adolescence and to provoke hostile, coercive, and frequent conflict between siblings (Boer, Goedhart, & Treffers 1992;Brody, Stoneman, & McCoy, 1992;Feinberg, Reiss, Neiderhiser, & Hetherington, 2005;McHale, Crouter, & McGuire, 1995;McHale et al, 2000). Rauer and Volling (2007), who studied 200 young adults aged 18-22 years, reported that parental differential affection was strongly related to feelings of jealousy toward one's sibling.…”
Section: Unequal Parental Treatment Narcissism and Sibling Relationmentioning
confidence: 99%
“…One explanation for the participants' reported dissatisfaction with the social support within their single-mother households may be because of the stage of physical development of the participants who being adolescents were in search of their identity (male identity for that matter) which cause them to experience conflicts with their opposite-sex parents (their mothers) (Bojuwoye, & Sylvester, 2012). McHale et al (2000) note that as adolescents go through the process of identity formation and trying to assert their independence from their parents they may encounter strains in their relationships with the parents. Bojuwoye et al (2012) also report that adolescent boys in single-mother households often find communication with their oppositesex parents very difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Our sample allowed further refinement, such as distinguishing between pleasurable and task-related activities in parents' differential time involvement. In line with research of Koch (as cited in McHale et al, 2000) that first and second born children differ in family responsibilities, we included responsibility of the sibling as an aspect of household responsibilities. Also, children expressed ambiguity with regard to direct parental control, viewing both its beneficial aspects for development and its token of parental involvement, as well as the unpleasantness of the confrontation with boundaries.…”
Section: Main Findingsmentioning
confidence: 99%